MARCH 2012 PLACEMENT ADS (The Accounting Review, 2012)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on ″Career Center,″ or call our office at 941-921-7747.UNIVERSITY OF WATERLOO invites applications for a tenured or tenure-track position in Assurance, for an appointment beginning 2012. Candidates for the tenured position should have established reputations for high-quality research and teaching, and an interest in contributing to our Ph.D. program. Candidates for Assistant Professor should have a Ph.D. or have completed their Ph.D. by the first date of their appointment at the University of Waterloo and should demonstrate the potential for high-quality research and teaching. Since 2008 we have hired 14 new faculty and in 2009 we added over 50,000 square feet of new classrooms and offices. We offer a stimulating environment for research and teaching, and promote intellectual curiosity and growth. The School's award-winning faculty includes active researchers using archival, experimental, and analytical techniques to study a broad spectrum of accounting and finance issues. Our faculty serve on the editorial boards of leading scholarly journals. The School's collaborative environment encourages faculty members to help each other reach their maximum potential. Our highly regarded and unique undergraduate and graduate programs attract top students from Ontario and across Canada. For details about our faculty and programs please visit: http://saf.uwaterloo.ca. The University of Waterloo consistently ranks as a leading comprehensive university in Canada and an innovator in education and research. It is located in Waterloo, Canada (designated as the 2007 Intelligent Community of the Year by the Intelligent Community Forum), a one-hour drive from Toronto, Canada's financial and cultural capital. To apply, interested candidates are required to include a curriculum vitae and a research sample to complete an online application at https://artsonline.uwaterloo.ca/OFAS/SAF/. Referees please send reference letters separately to: heidi@uwaterloo.ca. Review of applications will continue until the position is filled. The University of Waterloo encourages applications from all qualified individuals, including women, members of visible minorities, native peoples, and persons with disabilities. Canadian citizens and permanent residents receive priority.UNIVERSITY OF NORTH TEXAS (UNT), Department of Accounting (http://www.cob.unt.edu/acct) in Denton, TX (DFW Metroplex) invites applications for a tenure-track faculty position at the Associate/Full Professor rank. The successful candidate will provide leadership for the program in Taxation, including engaging with alumni and professionals, and mentoring junior faculty and doctoral students. The Department of Accounting at UNT is committed to academic excellence and diversity within their faculty, staff, and student body. The Department of Accounting offers a full range of academic degree programs including Bachelor of Accounting (B.B.A.), professional 150-hour program (B.S./M.S.) in Taxation or Accounting, M.S. in Taxation or Accounting, and an Accounting doctoral program. Our programs are among the most innovative in the country, our faculty exhibit expertise in a host of accounting disciplines, and the department is separately accredited by AACSB. Candidate must hold a doctorate in Accounting (or equivalent) with an established high-quality archival academic publication record and have demonstrated the ability to work with others in developing and conducting high-quality research. CPA, CMA, CIA, or equivalent certification is preferred, but not required. Review of applicants will begin immediately and continue until the position is closed. Salary is competitive and commensurate with qualifications. Contact person: Dr. Don W. Finn at Don.Finn@unt.edu or (940) 565-3084. Apply online at: https://facultyjobs.unt.edu/applicants/jsp/shared/Welcome_css.jspBRADLEY UNIVERSITY, Foster College of Business invites applications and nominations for a tenure-track faculty position in accounting. Bradley University is a distinctive, medium-size, comprehensive private institution of higher learning located in Peoria, IL with 5,000 undergraduate and 1,000 graduate students. A Ph.D. or D.B.A. or near completion with emphasis in accounting is required. Professional certification (CPA, CMA, or CIA) is desirable. Primary teaching needs are in Financial Accounting and Auditing, but candidates must be able to teach in another area. Demonstrated excellence in teaching and scholarly research is required for tenure and promotion. Salary is AACSB-competitive. Position is available Fall 2012 with teaching opportunities available at both the undergraduate and graduate levels. Interested applicants should submit a letter of application, current vita, transcripts, and contact information for three professional references to: Dr. John Gillett, Chair, Department of Accounting, Bradley University, 427 Baker Hall, Peoria IL 61625. Screening of applications will begin immediately and continue until the position is filled. For additional information, please visit http://www.bradley.edu. Bradley University is an Equal Opportunity/Affirmative Action Employer. The administration, faculty, and staff are committed to attracting qualified candidates from groups currently under-represented on our campus.WEBER STATE UNIVERSITY seeks applicants to teach in the areas of tax or auditing; execute scholarship in field; provide service to university, community, and profession. ABD in accounting with expectation of completion of Ph.D. or D.B.A. within one year required. Area of emphasis in either tax or audit. Degree must be from a regionally accredited institution. Provide evidence of teaching effectiveness. To apply, complete the online faculty/staff data form at: http://jobs.weber.edu and attach a letter of application that addresses your qualifications for teaching tax and/or audit, a cv, and the names and contact information for three references. Screening of applications will begin December 18, 2011. Position will remain open until filled. Criminal background check required as a condition of employment. WSU is an AA/EOE.UNIVERSITY OF ILLINOIS AT CHICAGO, Department of Accounting invites applications for tenured or tenure-track faculty positions beginning August 16, 2012. The rank of the positions is open. At the Assistant Professor level, a Ph.D., completed or near completion, and strong potential for quality research and teaching is expected. Applicants at the Associate or Full Professor level must have a Ph.D. and an excellent record of scholarly research activity and teaching consistent with a senior-level faculty appointment. The position will encompass: research; undergraduate and graduate teaching; service to the department, college, and university; and outreach to the business communities. Additional information about the department, college, and university can be found at our website: http://www.uic.edu/cba/accounting This search will begin immediately. For fullest consideration, please apply to: https://jobs.uic.edu/ by January 6, 2012, attach a letter of interest, curriculum vitae, representative publications, and references. Only completed applications will be considered. For information about these positions, please free to contact: Professor Somnath Das, Head of the Department at: sdas@uic.edu. UIC is an AA/EOE.UNIVERSITY OF WYOMING, Department of Accounting invites applications for a full-time, tenure-track Assistant Professor with teaching and research interests in any area of accounting. Candidates should have an earned doctorate in accounting from an AACSB-accredited institution (or ABD nearing completion). Relevant professional experience is also highly desired (CPA preferred). A competitive salary is available for a nine-month contract plus the University of Wyoming's excellent benefits package. Qualified candidates should mail an application letter (refer to position #0642), three recommendation letters, curriculum vitae, and summaries of teaching performance to: Kenton Walker, Department of Accounting, Dept. 3275, 1000 East University Avenue, Laramie, WY 82071; or via email: kbwalk@uwyo.edu. Appointments are anticipated for Fall 2012. Job Requirements: Teaching 50%, Advising 2%, Research 48%. For more about the department and its programs, visit: http://www.uwyo.edu/accounting. UW conducts background investigations on prospective employees. UW is committed to diversity and endorses the principles of affirmative action.MISSISSIPPI STATE UNIVERSITY–MERIDIAN seeks applicants for a tenure-track position beginning January 1, 2012 or as soon thereafter as mutually agreeable. Minimum qualifications: Doctorate in Accounting from an AACSB-accredited institution or Doctorate in Business Administration with an emphasis in Accounting from an AACSB-accredited institution with demonstrated excellence in the field of accountancy. Preferred qualifications: Professional certification and practical experience in accounting. Responsibilities: Teach a variety of undergraduate and graduate courses in financial/managerial accounting (3/3 teaching load), publishing in peer-reviewed journals, and advising and mentoring students. Summer employment is frequently available; however, it is not guaranteed. Salary range is 90,000–120,000 for nine-month employment. Review of applications will begin immediately and continue until position is filled. Interested applicants must complete the Personal Data Information Form online at: http://www.jobs.msstate.edu, and send: (1) letter of application; (2) vitae; (3) official transcripts; (4) three letters of recommendation; and (5) the name, address, and telephone number of three additional references to: Dr. Kevin Ennis, Search Committee Chair, Division of Business, MSU-Meridian, 1000 Highway 19 North, Meridian, MS 39307. MSU is an AA/EOE.SOUTHERN POLYTECHNIC STATE UNIVERSITY, Business Administration Department invites applications for a tenure-track Assistant Professor position in Accounting beginning August 2012. This position is subject to availability of funding. Applicants must possess an earned doctorate degree in accounting as well as a CPA license. Preference given to AACSB- or ACBSP-accredited school. Applicants should have a commitment to excellence in teaching, applied research, and experience developing instructional materials. Applicants should submit an application letter; vitae; three professional references who may be contacted; evidence of teaching effectiveness; and unofficial transcripts. Applications materials must be submitted online. Please visit our HR website at: http://www.spsu.edu/hr/faculty.html for details and position requirements. Southern Polytechnic State University is a member of the University System of Georgia. The university is located 20 minutes northwest of Atlanta, GA. Southern Polytechnic is an EOE/ADA/AA.UNIVERSITY OF SOUTH DAKOTA, Beacom School of Business is currently seeking applicants for a full-time, tenure-track Assistant Professor of Accounting beginning August 22, 2012. A doctorate in accounting from an AACSB International accredited program is required, although ABD with a completion date as approved by the department chair will be considered. Primary teaching responsibilities include graduate and undergraduate financial accounting courses. Applicants are required to attach: (1) letter of application, (2) vita, (3) college transcripts (copies accepted) showing highest degree earned, (4) writing sample, and (5) contact information for three references (include email addresses and current telephone numbers). Only online applications will considered for the position. Applicants can visit us at: for information should be to: The University of is an and committed to the diversity of the faculty, staff, and OF SOUTH seeks applicants for a nine-month Assistant or Associate Professor position to teach accounting at the and/or beginning August 16, 2012. is located in as well as is of the International Business of The a with over is a with excellent and private Review of applications immediately and until positions are filled. transcripts will be required date as well as a background Ph.D. in Accounting or a field from an AACSB-accredited institution. will be considered for tenure-track position of applicants must be qualified AACSB and must demonstrate a commitment to teaching excellence and to publishing in journals. Applicants must also demonstrate ability and commitment to to the Professional certification in professional and ability to work with students and the professional Review of applications immediately and until positions are filled. transcripts will be required date as well as a background to UNIVERSITY, School of invites applications for an Assistant Professor position in Accounting for Fall 2012, Candidates must have (or a Ph.D. degree by appointment by Fall 2012. research as by publication in the accounting is expected. Research is with a teaching The School of is AACSB-accredited and research with to and other The University offers and Ph.D. programs in accounting. details are available at: three from and one from and is a area with materials to be submitted Interested candidates should a curriculum and other to the position at: University is an UNIVERSITY is seeking applications for tenure-track faculty positions or Associate and anticipated positions in accounting. areas of teaching will be considered audit, or The anticipated date of appointment for these positions is Fall 2012. the University and the University is the University in and well for its quality of education and students. The University is located at Business School offers degree programs at the and Ph.D. levels. information about the and current faculty can be found at: Job Candidates for a tenure-track Assistant Professor position should have a commitment to excellence in teaching and scholarship and either a Ph.D. in accounting or degree in Summer 2012. Candidates for the position should have a commitment to excellence in teaching and either (1) a degree with professional experience and professional certification or (2) a Ph.D. in accounting. Please send your to: Professor of at email: OF School of is seeking candidates for a position at the Assistant or Associate Professor rank for Fall 2012. doctorate in a high-quality research ability and interest to teach in any accounting with the of Taxation required. For consideration, please send a letter of interest with a three a sample or of teaching and of or representative research to: of the School of College of Business and University of The University of is an Equal and encourages applications from and UNIVERSITY, School of at invites applications and nominations for tenure-track positions in accounting Fall 2012. Preference will be given to and although all ranks as well as all areas will be considered. of the positions is subject to Salary will be commensurate with experience and The candidate should possess an earned doctorate from an accredited institution in accounting and demonstrate potential to a record of research and professional consistent with an appointment for the rank. and applications are at: of the application should be to: the search can be to: Chair, Search Committee at: or Review of applications will begin immediately and continue until the positions are filled. The Accounting Area is for excellence in scholarly research in accounting and the and of high-quality degree At are 20 faculty members in the area. by in the top of all AACSB-accredited business the School of is one of of business that is accredited in both business and accounting by the to of Business STATE UNIVERSITY seeks applicants for an Professor of Accounting position to teach and scholarly research in the area of financial and teach of accounting courses each academic Teaching includes teaching courses in financial accounting at undergraduate and graduate levels. of scholarly in financial accounting and the research teaching. scholarly research and to the intellectual and professional of the Department of Accounting, the College of Business, State University, and the other as by the department Minimum ABD doctorate in accounting or other business completion of degree by November 1, evidence of scholarly research; and teaching experience in financial accounting or other business field at the university Additional Preferred Ph.D. or D.B.A. in accounting from an AACSB-accredited teaching experience at the university record of in in the accounting area and/or evidence of other scholarly CPA or other accounting CMA, CIA, To apply, contact: Dr. at or email: UNIVERSITY, School of Business invites applications for a tenure-track Assistant Professor position in the Accounting department to begin in Fall 2012. Candidates should have a strong interest in research and teaching to one of the business as contract or financial and of accounting information and financial and The faculty member will teach undergraduate and courses in the relevant and research in one of the areas of the business school. Qualified candidates must hold a doctorate from a research institution August and provide evidence of strong potential for excellence in research and teaching. Applications should include a full curriculum vitae, of research three letters of and evidence of teaching effectiveness. Please submit the to at: University is an and invites applications from and OF seeks a tenure-track Assistant Professor of The position a Ph.D. in accounting and an active research who are ABD may apply, but are to complete all degree within months of the Candidates with a in accounting are to faculty are to scholarly research for and an active in curriculum The College of Business Administration accredited by AACSB and offers both undergraduate and graduate The immediately and will continue until the position is filled. To for an please contact: Dr. College of Business University of W. or or Please provide a cv, and the names and contact information for three professional references. most comprehensive private university, the University of is an institution of higher education by the of and the of The University seeks qualified candidates who will to the and academic The University of is an with a faculty and student and persons of all information is available at and School of Business invites applications for a full-time, tenure position or a contract position in Ph.D. but ABD may be considered. Candidates with CPA are Position August 2012. include teaching the and advising and on faculty as well as service to the and to the Salary and benefits are For more information and to apply, visit: College is an International Summer School invites applications for Professor positions in top University, University of International Business from to August 2012. The teach two courses. salary of we each Professor to teach two to three free the of teaching; free for and a member the and in for and in for for and and for within one teaching one to help with your needs in are interested in us as a teaching faculty member please a of your curriculum vitae to: we receive your cv, we will to within three business have any our 2012 please contact us at: or at we will be to your in is a by to offer Please visit our official at: OF School of is seeking applications for a teaching faculty position in the area of include Ph.D., or professional accounting prior teaching experience in and strong with tax of teaching excellence in and should be materials including a letter of interest, vita, and evidence of teaching should be submitted online at: reference letters should be separately to: School of University of Hall, or to: Screening will begin immediately and continue until the position is filled. The University of is an Applications from and candidates are for this position. To please contact the at OF School of is seeking applications for a tenure-track faculty position at the Assistant Professor level for Fall 2012. Candidates for the position must have an interest in and/or Financial Accounting, and be committed to high-quality scholarly research. Applications are from Assistant as well as new or nearing completion of their Ph.D. Salary and research are materials including a letter of interest, vita, evidence of teaching and a sample of should be submitted online at: reference letters should be separately to: School of University of Hall, Screening will begin immediately and continue until the position is filled. The University of is an Applications from and candidates are for this position. To please contact the at OF School of Business the College of invites applications for tenure-track positions in Accounting at the rank of The is accredited by the AACSB. A new M.S. in Accounting program will in 2012. the to an Accounting to its new Ph.D. in Business and to a new instructional within the with an of is located about northwest of Requirements: an earned Ph.D. or D.B.A. in Accounting or a by the date 2012 or a demonstrated record or at the Assistant level a strong potential high-quality research; a demonstrated record of high-quality in of Accounting, Auditing, or at both the graduate and undergraduate excellent and the ability to and the ability to work with a student and faculty given to candidates with accounting or with CPA, CMA, Applicants should apply online at: a (1) a of professional interests and (2) cv, (3) of research, (4) teaching and evidence of teaching effectiveness. Applications until the posting is UNIVERSITY OF School of Business and invites applications for tenure-track position in Candidates should have a Doctorate as well as an active research Salary range commensurate with qualifications and Accounting applicants should have a doctoral degree in Accounting also with expertise in one or more of the audit, and or other Position teaching, research, and service including teaching at and undergraduate levels. or experience with an and may be required as of the teaching To apply, please visit: To be considered will to your cv, and three references. For information about this please contact: Dr. Associate and Chair, Search Review of applications will begin January 2012 and will continue until positions are filled. University of is an committed to excellence and in its is seeking applicants for a tenure-track position beginning Fall 2012. areas of will be considered. A Ph.D. in Accounting is required. Preference will be given to with at two of professional work experience and a For all positions, tenure and rank are commensurate with the qualifications and Salary and benefits are Candidates must demonstrate potential to research as by in or work in Teaching excellence and a to in service are will be considered at the rank of must complete the doctoral degree by the of the first academic year of appointment. The candidate be to teach both undergraduate and graduate courses. Candidates can apply by our website at: to submit the required materials. Preference will be given to applications by 2012. Review of applications will continue until the position is filled. College is an and encourages women, persons of and to apply for ILLINOIS UNIVERSITY, Department of Accounting and invites applications for a tenure-track Professor of Primary teaching is in financial with a area in or Preference will be given to candidates with professional degree from an AACSB-accredited institution is required. A record of teaching and scholarship at the Full or Associate Professor level is also required. The business and accounting programs are accredited by AACSB teaching is A competitive salary and an excellent benefits are Screening January 2012 and will continue until the position is filled. date is August 2012. For complete details or contact: a that includes or UNIVERSITY, School of Business, Department of Accounting, Taxation, and in Business invites applications for an anticipated tenure-track position in the graduate program in accounting or at the Associate or Full Professor level beginning Fall 2012. The candidate will be to teach Candidates must hold either a Ph.D. in Business from an AACSB-accredited program with an accounting or or a with a Please send a letter of interest, curriculum vitae, evidence of teaching excellence and scholarly and the addresses and telephone of three references to: Dr. Department of Accounting, Taxation, and in Business at: University is an committed to diversity in its faculty, staff, and student and encourages applications from the spectrum of a AT School of Business Administration and invites applications for two tenure-track positions in accounting at the Assistant Professor level beginning Fall 2012. we may candidates at the Associate Teaching responsibilities include courses consistent with the academic and professional experience at both the undergraduate and graduate levels. areas of teaching and research in accounting will be considered. A Ph.D. or D.B.A. in Accounting from an AACSB-accredited institution with degree in by August 2012 is required. will be considered degree completed within months of required qualifications include scholarly potential in accounting demonstrated by or high-quality and research ability to teach in a and strong work and commitment to Preferred qualifications include professional certification as a CPA, or other professional accounting interest in teaching in the area of potential for teaching graduate and relevant work and degree in by August 2012. Apply online at: should include cv, three transcripts, and teaching should be to: positions are subject to Review November 1, 2011. until filled.